Patterns of Addiction in Chronic Skin Diseases: A Comparative Analysis of Addictions and Influencing Factors in Atopic Dermatitis and Psoriasis - Roxana Mazilu; Stefanie Ziehfreund; Tilo Biedermann; Alexander Zink (Acta Dermato-Venereologica)
Addictions seem to be more frequent in atopic dermatitis and psoriasis patients than in the general population. This cross-sectional observational study comparatively evaluated substance-related and behavioural addictions in atopic dermatitis and psoriasis patients and analysed possible addiction patterns. From October 2023 to April 2024, 100 atopic dermatitis and 104 psoriasis patients at a German university hospital completed an anonymous questionnaire, including sociodemographic and health-related parameters, along with validated assessment tools for common addictions (smoking, gambling, alcohol, drugs, food, and internet). More psoriasis patients had at least 1 addiction (50.0% vs 39.0%), were more frequent daily smokers (34.6% vs 15.0%) and reported gambling more frequently than atopic dermatitis patients. No differences emerged regarding gambling addiction. Psoriasis patients showed higher body mass index, with 1.9% addicted to food. Atopic dermatitis patients were more vulnerable to pathological internet use (9.0% vs 2.9%). Low happiness was a risk factor for smoking in atopic dermatitis and for gambling and drug consumption in psoriasis patients. Low disease severity was associated with pathological alcohol in-take in psoriasis. Younger age emerged as a ubiquitous risk factor for drug consumption. Distinct addiction patterns in atopic dermatitis and psoriasis patients, influenced by age, happiness, and disease severity, should guide the development of education and screening strategies.